The Potential for Forest Healing in Pelawan Forest Biodiversity Park (Kehati) in Central Bangka-Based on SNI 9006:2021 Concerning Forest Tourism - Cahyani, Dwi Rizky; Apridian, Ega; Rahman; Syahri, Arian (Universitas Airlangga, 2025)
This research aims to analyze the suitability of the Pelawan Forest Conservation Park as a Forest Healing Site based on biophysical parameters established in SNI 9006:2021. The urgency of this study arises from the global rise of wellness-based tourism and the growing scientific evidence that forest therapy improves both physiological and psychological health. Although Forest Healing has been widely implemented in Japan, South Korea, and Europe, research in humid tropical ecosystems, particularly in Indonesia, remains limited, creating a significant knowledge gap regarding the applicability of standardized forest therapy criteria in these environments. Field observations and spatial analyses were conducted across three zones within the Pelawan Forest to measure vegetation density, temperature, humidity, slope, and noise. The results indicate that the forest meets several key SNI parameters: vegetation density is categorized as dense (80–93%), humidity remains within the ideal range, slope conditions are classified as sloping (8–15%), and noise levels are low (35.37 dB). However, the average temperature (27.33°C) slightly exceeds comfort standards. Overall, the Pelawan Forest demonstrates strong potential as a Forest Healing site, though further seasonal and microclimate assessments are recommended to enhance accuracy and support sustainable forest-therapy development.